New approach to training in citizen security from the social link university–community - Edicta Gregoria González-Leal; María Elena Pardo-Gómez; José Manuel Izquierdo-Lao (Maestro y Sociedad, 2017)
This article bases the need for a new conception in the training approaches in the training institutions of citizen security professionals, due to the present changes in the 21st century at the state, regional and local level, where the protagonism of the same lies In responding to the new challenges, trends and challenges present in society. It also analyzes the significance of the university's social connection with the communities, so that the praxis of the students goes beyond the understanding of the problems to the search for possible alternatives for their solution, with the consequent social transformations that this bring along.